Vertical ground reaction forces, paw pressure distribution, and center of pressure during heelwork in working dogs competing in obedience - Charalambous, Danae; Lutonsky, Christiane; Keider, Stefan; Tichy, Alexander; Bockstahler, Barbara (Frontiers in Veterinary Science, 2023)
Heelwork walking is a command that competitive obedience and working dogs are trained to perform. Unlike other canine sports, the research for competitive obedience sport is limited and no research regarding biomechanical gait adaptions during heelwork walking has been published. The aim of the study was to investigate the changes in vertical ground reaction forces, paw pressure distribution (PPD), and center of pressure (COP) of Belgian Malinois during heelwork walking. Ten healthy Belgian Malinois were included in the study. The dogs walked first without heeling (normal walk) and then while heeling on a pressure platform. The comparison between normal and heelwork walking was performed using mixed-effects models. Post hoc analyses were performed using Sidak’s alpha correction procedure. During heelwork walking, a significant decrease in the vertical impulse and stance phase duration (SPD) and a significant increase in the craniocaudal index and speed of COP was observed in the forelimbs compared to normal walking. At the hindlimbs, a significant increase in vertical impulse and SPD was observed during heelwork walking. Regarding PPD, a significant decrease of vertical impulse was observed at the cranial quadrants of the right forelimb and craniolateral quadrant of the left forelimb during heelwork. The area was significantly decreased at the craniolateral quadrant of the left forelimb and the time for the peak vertical force was prolonged significantly at the caudal quadrants of the right forelimb during heelwork walking. The vertical impulse was significantly increased in all quadrants of the hindlimbs except the craniolateral quadrant of the left hindlimb. The effect of these changes on the musculoskeletal system of working dogs should be investigated in further studies, using electromyography and kinematic analysis.